2010
DOI: 10.1158/0008-5472.can-10-1348
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression and Clinical Outcomes in Patients Treated with Adjuvant Chemotherapy after Complete Resection of Non–Small Cell Lung Carcinoma

Abstract: This study determined whether expression levels of a panel of biologically relevant microRNAs can be used as prognostic or predictive biomarkers in patients who participated in the International Adjuvant Lung Cancer Trial (IALT), the largest randomized study conducted to date of adjuvant chemotherapy in patients with radically resected non-small cell lung carcinoma (NSCLC). Expression of miR-21, miR-29b, miR-34a/b/c, miR-155, and let-7a was determined by quantitative real-time PCR in formalin-fixed paraffin-em… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
3
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(120 citation statements)
references
References 46 publications
8
106
3
3
Order By: Relevance
“…Patients were of a variety of carcinomas, including breast cancer, pancreatic ductal adenocarcinomas, esophageal cancer, hepatocellular carcinoma, leukemia, colorectal cancer, lung cancer and lymphoma. Of all the 28 studies, 16 studies (n = 2536) with HR data could be included for metaanalysis [7,[13][14][15][16][17][18][33][34][35][36][37][38][39][40][41]. Among them, seven studies (n = 1678) recruited lung cancer patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients were of a variety of carcinomas, including breast cancer, pancreatic ductal adenocarcinomas, esophageal cancer, hepatocellular carcinoma, leukemia, colorectal cancer, lung cancer and lymphoma. Of all the 28 studies, 16 studies (n = 2536) with HR data could be included for metaanalysis [7,[13][14][15][16][17][18][33][34][35][36][37][38][39][40][41]. Among them, seven studies (n = 1678) recruited lung cancer patients.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Heegaard et al reported miR-155 could only insignificantly predict outcome with HR more than 1 but P values more than 0.05 [17]. Moreover, a study recruiting 637 lung cancer patients even suggested higher miR-155 expression may indicate better survival but the trend did not reach significance (P = 0.39) [18]. Therefore, it is necessary to conduct a systematic review and meta-analysis to summarize the findings globally and address the inconsistencies of literature.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have corroborated this finding in lung cancer and other malignant diseases including colorectal cancer, breast cancer, hepatocelluar carcinomas, pancreatic ductal adenocarcinomas and adult T-cell leukemia (Raponi et al, 2009;Greither et al, 2010;Shibuya et al, 2010;Chen et al, 2012;Han et al, 2012;Huang et al, 2012;Ishihara et al, 2012;Papaconstantinou et al, 2012); however, other reports provided insignificant or opposite evidences (Jung et al, 2009;Voortman et al, 2010;Donnem et al, 2011;Saito et al, 2011;Monsálvez et al, 2012;Shinmei et al, 2012). In order to investigate the precise association between miR-155 expression and the prognosis of patients, we combined the HRs extracted from the eligible data, and found that patients with high miR-155 expression were likely to have an unfavorable outcome.…”
Section: Has Prognostic Value In Patients With Nsclcs and Digestive Smentioning
confidence: 87%
“…Although the sample number in our study was rather small, low miR-29b tumor levels significantly correlated with poor event-free and overall survival, whereas high miR-29b tumor levels were associated with favorable outcome. A recent study found no prognostic role for miR-29b in patients treated with adjuvant chemotherapy after complete resection of lung cancer (Voortman et al, 2010). However, patients had different histological subtypes, and the study used a different control gene for standardization and a different cut-off value.…”
Section: A549 Anti Mir-29bmentioning
confidence: 99%